The usefulness of case in plastic user interfaces - Mitchelmore, Robert Eurig (2016)
This thesis addresses a problem that faces developers of applications for mobile devices. There is an ever-increasing number of mobile platforms and form factors in the world, and mobile developers have to build applications that can be used on as many of these as possible while still retaining usability. Furthermore, because of constraints put on the development process by the companies that develop the mobile platforms, there is an absolute requirement that the applications produced by the tool conform to the user interface guidelines for each platform. To address this problem, this thesis uses the concept of “case”, which is a phe- nomenon from natural language. In natural languages, case has many functions and plays a part in many systems. This thesis engages with case in one of these functions: it permits flexible word ordering. Case is used here to allow flexible or- dering of elements within the user’s dialogue with the machine. Case may either be useful because of some analogical process in the developer’s head or because of deeper ideas in linguistic theory. To evaluate this idea, a suitable case system was embedded in a tool and this tool was used in three distinct contexts. First, applications were built for three external companies. Second, a workshop study was done with external developers. Third, more external developers were given the tool for a longer period to produce an application of their choosing. These three contexts gave an excellent view into the use of the case system during the development of applications. This evaluation showed that the kinds of functions that case describes are rel- evant to describing user interfaces; that it is possible to implement a plausible case system usefully in a software tool, at least for mobile development; that the case system when embedded within the tool can be used to build useful applications; and that case can be used and understood by developers other than the author.